Head over heels but I forget why: Disruptive functional connectivity in older adult fallers with mild cognitive impairment - Crockett, Rachel A.; Hsu, Chun Liang; Best, John R.; Beauchet, Olivier; Liu-Ambrose, Teresa (Behavioural brain research, 2019)
•Fallers with MCI had a greater level of disruptive DMN-SMN connectivity.•DMN-SMN connectivity increased linearly from Fallers only – MCI only – Fallers + MCI.•Fallers with MCI have significantly greater postural sway than those without MCI.•Postural sway increased linearly from Fallers only - MCI only - Fallers + MCI. Disrupted functional connectivity has been highlighted as a neural mechanism by which impaired cognitive function and mobility co-exist in older adults with mild cognitive impairment (MCI). The objective of this study was to determine the independent and combined effects of MCI and faller status on functional connectivity of three functional networks: default mode network (DMN), fronto-parietal network (FPN) and sensorimotor network (SMN) between 4 groups of older adults: 1) Healthy; 2) MCI without Falls; 3) Fallers without MCI; and 4) Fallers with MCI. Sixty-six adults aged 70–80 years old were included. Cognition was assessed using: 1) cognitive dual task; 2) Stroop Colour-Word Test; 3) Trail Making Tests (TMT); and 4) Digit Symbol Substitution Test (DSST). Postural sway was assessed with eyes opened and standing on the floor. Functional connectivity was measured using fMRI while performing a finger-tapping task. Differences in DMN-SMN connectivity were found for Fallers with MCI vs Fallers without MCI (p = .001). Fallers with MCI had significantly greater postural sway than the other groups. Both DMN-SMN connectivity (p = .03) and postural sway (p = .001) increased in a significantly linear fashion from Fallers without MCI, to MCI without Falls, to Fallers with MCI. Participants with MCI performed significantly worse on the DSST (p = .003) and TMT (p = .007) than those without MCI. Aberrant DMN-SMN connectivity may underlie reduced postural stability. Having both impaired cognition and mobility is associated with a greater level of disruptive DMN-SMN connectivity and increased postural sway than singular impairment.